Reactive polymers fundamentals and applications : a concise guide to industrial polymers - Fink, Johannes Karl (William Andrew is an imprint of Elsevier, 2018)
Reactive Polymers: Fundamentals and Applications: A Concise Guide to Industrial Polymers, Third Edition introduces engineers and scientists to a range of reactive polymers and then details their applications and performance benefits. Basic principles and industrial processes are described for each class of reactive resin (thermoset), as well as additives, the curing process, applications and uses. The initial chapters are devoted to individual resin types (e.g., epoxides, cyanacrylates), followed by more general chapters on topics such as reactive extrusion and dental applications. Injection molding of reactive polymers, radiation curing, thermosetting elastomers, and reactive extrusion equipment are covered as well. The use of reactive polymers enables manufacturers to make chemical changes at a late stage in the production process, which, in turn, cause changes in performance and properties. Material selection and control of the reaction are essential to achieve optimal performance. Material new to this edition includes the most recent developments, applications and commercial products for each chemical class of thermosets, as well as sections on fabrication methods, reactive biopolymers, recycling of reactive polymers and case studies.
Keywords: Gums and resins, Synthetic.; Gums and resins -- Industrial applications.; elektronické knihy; electronic books